Excess circulating alternatively activated myeloid (M2) cells accelerate ALS progression while inhibiting experimental autoimmune encephalomyelitis. - Ilan Vaknin (Public Library of Science (PLoS), 2011)
Background Circulating immune cells including autoreactive T cells and monocytes have been documented as key players in maintaining, protecting and repairing the central nervous system (CNS) in health and disease. Here, we hypothesized that neurodegenerative diseases might be associated, similarly to tumors, with increased levels of circulating peripheral myeloid derived suppressor cells (MDSCs), representing a subset of suppressor cells that often expand under pathological conditions and inhibit possible recruitment of helper T cells needed for fighting off the disease. Methods and findings We tested this working hypothesis in amyotrophic lateral sclerosis (ALS) and its mouse model, which are characterized by a rapid progression once clinical symptoms are evident. Adaptive transfer of alternatively activated myeloid (M2) cells, which homed to the spleen and exhibited immune suppressive activity in G93A mutant superoxide dismutase-1 (mSOD1) mice at a stage before emergence of disease symptoms, resulted in earlier appearance of disease symptoms and shorter life expectancy. The same protocol mitigated the inflammation-induced disease model of multiple sclerosis, experimental autoimmune encephalomyelitis (EAE), which requires circulating T cells for disease induction. Analysis of whole peripheral blood samples obtained from 28 patients suffering from sporadic ALS (sALS), revealed a two-fold increase in the percentage of circulating MDSCs (LIN(-/Low)HLA-DR(-)CD33(+)) compared to controls. Conclusions Taken together, these results emphasize the distinct requirements for fighting the inflammatory neurodegenerative disease, multiple sclerosis, and the neurodegenerative disease, ALS, though both share a local inflammatory component. Moreover, the increased levels of circulating MDSCs in ALS patients indicates the operation of systemic mechanisms that might lead to an impairment of T cell reactivity needed to overcome the disease conditions within the CNS. This high level of suppressive immune cells might represent a risk factor and a novel target for therapeutic intervention in ALS at least at the early stage.